(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article shows the features of education management, the basic concepts of management functions, higher education institution the need to focus on ensuring the quality of management of pedagogical personnel in higher education, increasing the effectiveness of interaction with them, ensuring their interest in the results of their activities.